Enhancing power conversion efficiency of DSSC by doping SiO2 in TiO2 photo anodes. (July 2015) - Balachandran, K.; Venckatesh, Rajendran; Sivaraj, Rajeshwari; Hemalatha, K.V.; Mariappan, R.
Abstract: A simple, less time consuming, cost ineffective sol–gel method was used to synthesis TiO2 nanoparticles (TiO2 ) and TiO2 –SiO2 nanocomposites (TiO2 –SiO2 ) using titanium tetra isopropoxide as TiO2 and silicic acid as SiO2 precursors respectively. The synthesized nanocomposites were characterized by XRD, SEM, TEM, UV–visible, FTIR and BET analysis. The quantum confinement effect of TiO2 and TiO2 –SiO2 was confirmed by a blueshift observed in UV–visible spectra. The band observed at 950 cm −1 in FTIR analysis confirmed the presence of Ti–O–Si bonds, the TEM analysis shows both the TiO2 and TiO2 –SiO2 were in nanometer size. The BET (Brunauer– Emmett–Teller) specific surface areas of the samples were 65 and 75 m 2 /g for TiO2 and TiO2 –SiO2 respectively. The power conversion efficiency (PCE) of the nanocomposites were studied by using Keithely electrometer and multimeter and it was found to be 2% and 2.5% for eosin-Y sensitized TiO2 and TiO2 –SiO2 nanocomposites respectively.